2013
DOI: 10.1080/13803395.2012.758239
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure, construct validity, and age- and education-based normative data for the Parametric Go/No-Go Test

Abstract: The Parametric Go/No-Go (PGNG) test assesses cognitive domains including attention and executive functioning with three levels of increasing difficulty. Level 1 measures accuracy and response time to three targets. Level 2 adds a nonrepeating rule, measuring response time to two targets, accuracy for targets, and accuracy for appropriate inhibition. Level 3 has three targets with the same nonrepeating rule. The task shows good construct validity, and factor analyses show adequate ability to distinguish between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
63
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 40 publications
10
63
1
Order By: Relevance
“…Langenecker et al (2007) found that better performance in the visual Go/NoGo is associated with better performance in the aforementioned tasks. This in line with other empirical studies that indicated consistent correlations of these tasks with the Go/NoGo paradigm (Barbarotto et al, 1998;Konishi et al, 1999;Morooka et al, 2012;Steinmetz & Houssemand, 2011;Votruba & Langenecker, 2013;Votruba et al, 2008). Also Konishi et al (1999) found similar activation in inferior prefrontal areas during the inhibition of Go trials as well as in the WCST.…”
supporting
confidence: 89%
“…Langenecker et al (2007) found that better performance in the visual Go/NoGo is associated with better performance in the aforementioned tasks. This in line with other empirical studies that indicated consistent correlations of these tasks with the Go/NoGo paradigm (Barbarotto et al, 1998;Konishi et al, 1999;Morooka et al, 2012;Steinmetz & Houssemand, 2011;Votruba & Langenecker, 2013;Votruba et al, 2008). Also Konishi et al (1999) found similar activation in inferior prefrontal areas during the inhibition of Go trials as well as in the WCST.…”
supporting
confidence: 89%
“…Research assessing impulsive behavior in humans through prepotent response inhibition tasks shows that performance in these tasks steadily improves (reduction in reaction times and commission errors rates) from childhood to young adulthood (Jaeger, 2013; LĂłpez-Caneda et al, 2014) and starts to decrease in later adulthood (Votruba & Langenecker, 2013). Inhibitory control seems to start maturing at around age 14 (Fischer et al, 1997; Luna et al, 2004; Munoz et al, 1998).…”
Section: Impulsive Behavior Across the Lifespan: Implications For mentioning
confidence: 99%
“…Votruba and Langenecker (2013) defined two types of outlying performance, skipping and fading. Skipping performance relates to omitting Go responses in favour of increased No-go accuracy and being characterised by excessively poor Go accuracy and near perfect No-go accuracy in one of the higher difficulty levels (2 or 3).…”
Section: Task Designmentioning
confidence: 99%
“…commission error rates of between 0.18 and 17.70 %; Fallgatter and Strik, 1999;Heinzel et al, 2013;Mulligan et al, 2014), in addition to its lack of ecological validity (Langenecker et al, 2007;Votruba and Langenecker, 2013). The lack of context in determining the No-go target, i.e.…”
Section: Introductionmentioning
confidence: 99%